IMPLEMENTASI LOAD BALANCING DENGAN ALGORITMA EQUAL COST MULTI PATH (ECMP): Ali Ridho Gumelar, Anton, Ummu Radiyah - Jurnal, Redaksi Tim (KILAT, 2018)
The rapid development of the Internet requires a counterweight in maintaining connectivity and network stability. connectivity becomes one of the aspects that take priority in a network, and therefore the Internet connection on demand to always be stable and interference free, but not always a connection running smoothly and stable. Usually there are a variety of disorders within a network, hence the need for bakcup management of the network that are running so that if one impaired then there will be a backup. One that can be done is by using load balancing. Subyek taken in this study to focus on the implementation of the source network backup or backup Internet from the dependence of the internet service provider or ISP provider. Load balancing method using Equal Cost Multi-Path, research methods that used are library research, observation and interviews network of PT.Nipindo. As for the design begins with installing mikrotik here in after may be applied load balancing. Technical test carried out by using a ping test is performed to determine whether the connection is running well or not. The result of applying load balancing method shows ECMP load balancing goes well. Load balancing does not change the physical structure of an existing network, so it can produce optimal connections when an increase in traffic due to the balanced distribution of bandwidth.